A comment on "Discriminatory Lending: Evidence from Bankers in the Lab" - Francesca Lipari; Marcello Sartarelli (Institute for Replication (I4R), 2024)
Brock and De Haas (2023) study the effect of randomising applicant gender in small business loan applications that are reviewed by loan officers at a Turkish bank in a lab-in-the-field experiment based on real-life applications. The main re- sults are: first, that loan approval rates are not gendered (direct discrimination); second loan officers are 6 percentage point (26%) more likely to condition loan ap- proval to a guarantor when the applicant is a female rather than a male (indirect discrimination). In our computational replication we obtain the manuscript results. In addition, a robustness replication shows that the main results are partly driven by the role of loan types, job seniority and population differences among cities.
Keywords: C93; G21; G32; J16; L25; L26; O16; 330; Gender discrimination; lending; lab experiment; field experiment